Optimalisasi Tata Kelola Dana Kampung untuk Meningkatkan Kesejahteraan Masyarakat Lokal - Yeimo, Petrus; Lewerissa, Christina Martha; Suripatty, Petrus Izaach (Jurnal Studi Pemerintahan dan Akuntabilitas, 2025)
Purpose: To examine the application of good governance principles in village fund management and their impact on community welfare in Kampung Aikai, Papua Tengah. Methodology/approach: The research employed a descriptive quantitative approach, collecting data through questionnaires, structured interviews, and document analysis. A purposive sampling technique was used to select 52 respondents familiar with village fund planning and implementation. Results/findings: The findings indicate that the implementation of good governance principles in Aikai Village is relatively strong: transparency (75%), accountability (70%), and participation (80%). The impact on community welfare reached 72%, especially through improved basic infrastructure. However, challenges remain in documentation and comprehensive community involvement during program evaluation stages. Conclusions: The study concludes that village fund management in Kampung Aikai generally adheres to good governance standards, contributing positively to community welfare. Improvements are needed in accountability mechanisms and inclusive participation across all phases of program management. Limitations: The study is limited to one village, with a relatively small sample size, which may not fully represent broader patterns in other regions of Papua or Indonesia. Contribution: The study offers insights for improving village fund governance in remote regions through stronger capacity and participatory systems.